Al Islam wal Hukmaniyyah al Muassasah al Jayyidah - Muhammad Sulthoni Yusuf (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
The aim of this writing is to describe the relationship between religious ethics and good governance values to create a good corporate governance and good government governance. Some people argue that the implementation of the good corporate governance is not satisfactory yet, due to the lack of awareness of the government authority, private companies’ stakeholders, scholars, and society on the importance of the system for both government and non-government organizations. Therefore, to provide a comprehensive understanding to the scholars and practitioners, this paper attempts to explain the corporate governance anatomy, Islamic values, and social condition of Indonesian society, which may become an appropriate model of corporate governance for the private companies, government institutions, government, and non-government organizations.